Exploring Literate Lives: Returning to the Field. (June 2016) - Henderson, Robyn; Woods, Annette
Abstract : The challenges of conducting lengthy fieldwork in today's busy academic world have impacted the types of research that are able to be carried out. In particular, traditional educational ethnography has become problematic for research beyond initial doctoral research programs. This article analyzes data collected during a return to the field of a study about literate lives, 11 years after the initial data collection. It considers the implications of exploring people's lives over time.